Review of Recent Developments Regarding the Durability Performance of Eco-Friendly Geopolymer Concrete - Turki S. Alahmari; Tareg Abdalla Abdalla; Mohammed Ali M. Rihan (Buildings, 2023)
The 21st century has witnessed a substantial increase in the demand for construction materials, mainly influenced by the growing population. This increase in demand has resulted in higher prices for these materials and has also placed considerable burdens on environmental resources, prompting the search for eco-friendly and economically viable alternatives such as geopolymer materials to replace traditional materials like cement. The benefits of geopolymer materials as substitutes for cement in concrete extend beyond their exceptional durability. Initially, geopolymer was introduced to address the environmental impact arising from carbon dioxide emissions and the substantial consumption of fossil fuels through the production of cement. The current review investigates recent advances regarding the durability characteristics of geopolymer materials. This includes aspects such as water absorption, temperature resistance, sulfuric acid resistance, sulfate resistance, chloride ion penetration, and freeze–thaw resistance, among others. The results of this review highlight geopolymer concrete’s enhanced durability over traditional cement-based concrete. Furthermore, this review offers recommendations and outlines potential research avenues for further exploration of geopolymer concrete.